2005
DOI: 10.2463/mrms.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Gd-EOB-DTPA Enhanced MRI for Hepatocellular Carcinoma: Quantitative Evaluation of Tumor Enhancement in Hepatobiliary Phase

Abstract: Objective: The purpose of this study was to evaluate the utility of gadolinium-ethoxybenzyl-diethylenetriamine pentaacetic acid (Gd-EOB-DTPA)-enhanced magnetic resonance imaging (MRI) for the quantitative evaluation of hepatocellular carcinoma (HCC) and dysplastic nodules in the hepatobiliary phase.Material and Methods: The subjects comprised 12 patients with 27 lesions (22 HCCs and 5 dysplastic nodules). Chemical-shift-selective fat-suppressed T 1 -weighted sequences were obtained before and 10, 20, and 40 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
106
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(113 citation statements)
references
References 21 publications
7
106
0
Order By: Relevance
“…Approximately 10 to 20z of conventional HCCs can show high intensity or take up gadoxetic acid during hepatocyte phase imaging. 89 There have been reports that OATP-8, an anion transporter on the hepatocyte surface, is overexpressed in these lesions. 90,91 One study suggested that none of these lesions was poorly diŠerentiated HCC.…”
Section: Hccs Taking Up Gadoxetic Acidmentioning
confidence: 99%
“…Approximately 10 to 20z of conventional HCCs can show high intensity or take up gadoxetic acid during hepatocyte phase imaging. 89 There have been reports that OATP-8, an anion transporter on the hepatocyte surface, is overexpressed in these lesions. 90,91 One study suggested that none of these lesions was poorly diŠerentiated HCC.…”
Section: Hccs Taking Up Gadoxetic Acidmentioning
confidence: 99%
“…Hepatocellular carcinomas usually do not take up Gd-EOB-DTPA and appear as hypointense lesions in the hepatobiliary phase, as do other tumors without normal hepatocyte function. 11,12 However, some hepatocellular carcinomas can show hyperintense lesions in the hepatobiliary phase, as in the present case. 3 The mechanism of the uptake of Gd-EOB-DTPA is currently being researched.…”
Section: Discussionmentioning
confidence: 53%
“…Although Gd-EOB-DTPA generally accumulates in benign hepatocellular lesions, its accumulation has been reported in a part of hepatocellular carcinomas in the hepatobiliary phase. 1 The teams of Kitao 9 and Narita 10 reported that expression of OATP1B3 determines the uptake of Gd-EOB-DTPA in the hepatobiliary phase in hepatocellular carcinomas, and Kitao's group reported that the expression of MRP3 determines the excretion of Gd-EOB-DTPA in the hepatobiliary phase in hepatocellular carcinomas. 9 To the best of our knowledge, the expression of transporters in benign hepatocellular nodules is not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Use of a recently available liverspeciˆc contrast medium for magnetic resonance (MR) imaging, gadolinium ethoxybenzyl diethylenetriaminepentaacetic acid (Gd-EOB-DTPA), has become common in the evaluation of hepatocellular lesions. [1][2][3][4][5] The medium accumulates in partially benign hepatocellular nodules. 5 However, few reports describe theˆndings of Gd-EOB-DTPA-enhanced MR imaging for hepatocellular adenoma, 2 and to the best of our knowledge, no reports detail their correlation with pathologicalˆndings.…”
Section: Introductionmentioning
confidence: 99%